Tinjauan Fiqih Mawaris terhadap Pembagian Harta Warisan dalam Keluarga - Abul Ala Al-Maududi; Kuni Kyla Afifah; Muhammad Hibban Ataridan Hambal Arifin; Keisha Olivia Rama Putri; Hafizh Rafid Hardian (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
Inheritance (tirkah) is a sacred institution in Islam that tests a Muslim’s moral integrity and social responsibility. However, the implementation of Fiqh Mawaris in Indonesia often faces complex challenges when it intersects with the plurality of customary legal systems and contemporary sociological demands. This study aims to analyze the perspective of Islamic inheritance law on the practice of estate distribution within families in Indonesia and to evaluate the role of the Compilation of Islamic Law (KHI) as a bridge between Sharia norms and societal realities. Using a qualitative method through literature review (library research) of various scholarly sources from 2020 to 2026, this study found that Fiqh Mawaris is not merely a mathematical instrument based on the principles of Aul and Radd, but rather an ethical system aimed at maintaining distributive justice and family harmony. In practice, Indonesian society tends to adopt ishlah (reconciliation) mechanisms based on mutual consent (antaradin) to harmonize religious values with local wisdom. The presence of the KHI plays a crucial role as a unifying force for substantive law, providing legal certainty through progressive ijtihad, such as the application of substitute heirs and mandatory bequests. This study concludes that the adaptability of Islamic law in Indonesia remains within the framework of Sharia, where the harmonization of Islamic values, local traditions, and state regulations has successfully produced an inheritance system that is not only normatively rigid but also practical, inclusive, and capable of ensuring legal certainty and family harmony within a pluralistic society.